Metode Penelitian Empiris sebagai Pendekatan Evaluatif Terhadap Kebijakan Hukum Nasional - Widiastuti; Febri Emelia Naomi Tetelepta; Ismawanty Mustain; Heri Siswanto (Jurnal Impresi Indonesia, 2026)
Legal research in Indonesia has tended to be dominated by a normative approach that emphasizes the analysis of laws and regulations, principles, and legal doctrine. However, in the context of evaluating national legal policies, a normative approach is often insufficient to assess the effectiveness, implementation, and actual impact of a policy on society. This article aims to analyze the position of empirical research methods as an evaluative approach in assessing national legal policies, including their concepts, scope, research procedures, and advantages and limitations. Therefore, empirical research presents a relevant method because it can explain the relationship between legal norms and social reality. This article discusses the position of empirical research methods as an evaluative approach in assessing national legal policies, including their concepts, scope, research procedures, and advantages and limitations. The results of the discussion indicate that empirical research can be an important instrument in assessing the success of legal policies, particularly in terms of implementation effectiveness, public response, and resulting social impact. Therefore, empirical research needs to be strengthened within the Indonesian legal academic tradition so that national legal policies are not only normatively valid but also just and socially effective.